Open Latarjet-Patte Procedure for Anterior Shoulder Stabilization: Critical Steps and Pearls for the Walch Technique - Stefan Bauer MD; Charline Coron MD; Xavier Lannes MD; Gilles Walch MD; William G. Blakeney MD (SAGE Publishing, 2021)
Background: Latarjet is a term used for different techniques and modifications to expose the glenoid and to transfer and fix the coracoid. The procedure is intricate and technically demanding. Outcomes and complications are heterogeneous in the literature. A master technique, the Walch technique, has been practiced for decades, with outstanding long-term results and patient satisfaction. Indications: Documented anterior dislocations with evidence for emergency reduction, with or without hyperlaxity and confirmation of a traumatic capsuloligamentous lesion. Contraindications include voluntary dislocations and multidirectional instability without these criteria. The Instability Severity Index Score can guide decision making on whether Bankart surgery is sufficient. Large Hill-Sachs lesions may be an indication for additional remplissage. Technique Description: Three key maneuvers and 6 surgical stages need to be mastered for consistent results. Key maneuvers include: (1) arm positioning for all stages, (2) retractor placement, and (3) safe conjoint tendon releases. Six key stages include: (1) coracoid exposure and initial release; (2) osteotomy and subsequent release; (3) bone preparation; (4) subscapularis split and arthrotomy; (5) 360° scapula neck exposure; and (6) cornerstone drill hole positioning, fixation, and simple capsuloplasty. Specific arm positioning facilitates coracoid exposure, releases, subscapularis split, arthrotomy, and retractor insertion, as well as capsular repair. A 360° anterior scapula neck exposure is crucial to drill the inferior cornerstone hole (2.5 for 4.0 partially threaded cancellous screw) 7 mm medial to the articular surface with mandatory direction parallel to the articular surface. The bone block can be dialed to the exact position, preventing lateral overhang. The capsule is closed to the coracoacromial ligament stump in 45° of external rotation. Results: A series of >80 cases with minimum 1-year follow-up (range: 1-5 years) demonstrated excellent results. Outcomes were good to excellent (Subjective Shoulder Value >80% in 95% of cases; Constant score >90% and Rowe score > 90%) in keeping with the Walch results (>1000 cases). The complication rate was low: 1 early coracoid fracture (1.3%), no dislocation and neurological complications, no new arthritis or progression, and good coracoid position without lateral overhang. Conclusion: The Walch technique, although technically demanding, provides excellent, consistently reproducible results once the 3 key surgical maneuvers and 6 stages of the procedure are mastered.